Cultivating Job Satisfaction: Influence of Transactional Leadership in Nepali Commercial Banks - Chalise, Dhan Raj; Paudel, Vishal (Management Dynamics, 2023)
The transactional leadership style is a result-oriented approach to providing job satisfaction inside an organization while ensuring productivity. The present study aims to determine the dimensions of transactional leadership styles and the relationship between transactional leadership style and job satisfaction in the context of Nepali commercial banks. This research used a survey design to gather data from one hundred fifteen employees from Nepali commercial banks. The study utilized simple random sampling techniques, and data was collected using a questionnaire that required respondents to rate their level of job satisfaction with dimensions of transactional leadership styles using a five-point Likert scale. The study shows a significant relationship between dimensions of transactional leadership style and job satisfaction in Nepali commercial banks. This study concludes that transactional leadership is the most influencing leadership style for job satisfaction and suggests the exercise of transactional leadership style in Nepali commercial banks.